Wisdom of Local Food Ingredients as an Enhancer to Food Supply for Diabetes Mellitus Prevention - Handayani, Oktia Woro Kasmini; Hasbullah, Maisarah; Mardiana, Mardiana; Budiono, Irwan; Nugroho, Efa (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
The increase in cases and prevalence of children with DM increased 70 times (2010 - January 2023). The dominant factor is unhealthy food consumption, which is exacerbated by the limited diversity of healthy foods available on the market. The objectives of the study were 1) to obtain local food ingredients and food products to be utilized, 2) to obtain product prototypes, 3) to obtain selected products for DM prevention. Activities consisted of: 1) Determining local food ingredients with a qualitative approach, 2) Obtaining selected product formulas for limited environmental testing, with Formula testing through expert design, Selected formula production testing, Proximate testing, organoleptic testing, 3) obtaining products ready for field testing, with hedonic testing, Anova testing and Post Hoc testing. The results obtained: 1) local food ingredients to be utilized are large white sweet potatoes (Ipomoema Batatas) with food products in the form of sweet potato pie. The selected product is F5 (45% sweet potato, 20% wheat and 5% tapioca), based on laboratory results, the lowest carbohydrate, total fat and total energy content (average 47.82%, 21.23%, 397.89) and the highest fiber content (9.64%). In addition, there are differences in overall values (F: 6.033, sig 0.003), color values (F: 4.252, sig 0.016), aroma values (F: 6.247, sig 0.002) and taste values (F: 1.841, sig 0.162). Furthermore, the results of the Post Hoc test concluded that there were differences related to overall values, color, aroma and taste between products F5 and F6.